Assessing the experience of dyspareunia in the endometriosis population: the Subjective Impact of Dyspareunia Inventory (SIDI). Issue 9 (21st June 2022) - Facchin, F; Barbara, G; Buggio, L; Dridi, D; Frassineti, A; Vercellini, P
Abstract: STUDY QUESTION: Is the Subjective Impact of Dyspareunia Inventory (SIDI) a reliable tool to examine the experience of dyspareunia in the context of endometriosis? SUMMARY ANSWER: In this study, the SIDI showed good structural and psychometric properties, and thus can be used as a reliable questionnaire to assess the impact of endometriosis-related dyspareunia on multiple dimensions, such as sexuality and intimate relationships. WHAT IS KNOWN ALREADY: In the endometriosis population, dyspareunia has a tremendous negative impact on psychological health, overall sexual function and couple relationships. However, there is a paucity of tools that can be effectively used in either research or clinical practice to assess the subjective components of the dyspareunia experience, including coping strategies to deal with the pain. STUDY DESIGN, SIZE, DURATION: In this cross-sectional study, the validity of the SIDI was examined by considering the responses provided by 638 participants with endometriosis and dyspareunia, who participated in an online survey conducted between 8 November and 21 December 2021. Participants were recruited using snowball sampling that involved posting the invitation to participate in the study on the social media of a patient association. PARTICIPANTS/MATERIALS, SETTING, METHODS: Participants were women aged ≥18 with clinical or surgical diagnosis of endometriosis. The SIDI measures the subjective impact of dyspareunia and is composed of 16 items focused on the frequency of dyspareunia-related experiences in the last 6 months, rated on a 5-point Likert scale. Sexuality was assessed using the Female Sexual Function Index. Psychological health was measured using the Hospital Anxiety and Depression Scale and the Rosenberg Self-Esteem Scale. Sociodemographic and endometriosis-related information was collected using a researcher-made questionnaire. Statistical significance was set at P < 0.05. MAIN RESULTS AND THE ROLE OF CHANCE: Factor analysis revealed that the SIDI has a four-factor structure and allows for examining the impact of dyspareunia in terms of Sexual Concerns (Factor 1), Relationship Concerns (Factor 2), Partner Support (Factor 3) and Endurance of Pain (Factor 4). The SIDI showed good structural and psychometric properties (including internal consistency), was associated with sexual function and psychological health and was able to discriminate between participants with and without sexual dysfunction. LIMITATIONS, REASONS FOR CAUTION: Reasons for caution are related to the risk of self-selection bias depending on the study population and recruitment strategy. Moreover, all the information provided by the participants was self-reported, which may have affected the accuracy of the data collected, especially with regards to endometriosis-specific information. WIDER IMPLICATIONS OF THE FINDINGS: This study may provide a new brief tool that can be used by clinicians and researchers to assess the impact of dyspareunia from a multidimensional perspective and to consider subjective aspects that can be usefully integrated with information about pain severity, timing and localization. STUDY FUNDING/COMPETING INTEREST(S): There was no funding for this study. A.F. is the President of APE-Odv (Associazione Progetto Endometriosi-Organizzazione di volontariato (Endometriosis Project Association-Volunteer Organization)), the largest nonprofit endometriosis patient association in Italy. The other authors have no conflicts of interest. TRIAL REGISTRATION NUMBER: N/A.